2015
DOI: 10.1097/fjc.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment With Antihypertensive Agents Enhances the Effect of Qiliqiangxin on Chronic Pressure Overload–induced Cardiac Hypertrophy and Remodeling in Male Mice

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Traditional Chinese medication has a certain foundation in clinic with a long history and may set a new direction for therapeutic strategies. Previous study has indicated that QLQX, a traditional Chinese medication, had beneficial effect on chronic heart failure patients and could prevent the heart from adverse remodeling 14 , 17 . Here, in this study, we focused on the protective effect of QLQX in a rat model of genetic hypertension and found that QLQX could improve cardiac function and attenuate cardiac remodeling and fibrosis after one-year treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medication has a certain foundation in clinic with a long history and may set a new direction for therapeutic strategies. Previous study has indicated that QLQX, a traditional Chinese medication, had beneficial effect on chronic heart failure patients and could prevent the heart from adverse remodeling 14 , 17 . Here, in this study, we focused on the protective effect of QLQX in a rat model of genetic hypertension and found that QLQX could improve cardiac function and attenuate cardiac remodeling and fibrosis after one-year treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pathogenesis of NAFLD/NASH is complex and multifaceted, there is still difficulty in finding the appropriate treatment strategy. Hence, the current therapy for NAFLD, rather than direct treatment against NASH, mainly focuses on the control of metabolic features associated with NAFLD, including obesity, diabetes mellitus, hypertension, and dyslipidemia [171,172,173,174,175]. Although a vast amount of data about various candidates or targets for NAFLD/NASH therapy are pouring in worldwide, most studies have been mainly conducted in men only.…”
Section: Gender-based Therapy For Nafld/nashmentioning
confidence: 99%
“…Drugs such as diuretics, beta-blockers, calcium antagonists, angiotensin-converting enzyme inhibitors (ACEIs), and angiotensin receptor blockers (ARBs) are suitable for the initiation and maintenance of antihypertensive treatment. Of these drugs, only ACEIs and ARBs are known to improve left ventricular remodeling induced by continuous high blood pressure [ 3 ]. However, ACEIs can cause an irritating cough [ 4 ] and kidney damage under special conditions [ 5 ] and even angioedema [ 6 ].…”
Section: Introductionmentioning
confidence: 99%